2021
DOI: 10.1136/tsaco-2020-000659
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on injury prevalence and pattern in the Washington, DC Metropolitan Region: a multicenter study by the American College of Surgeons Committee on Trauma, Washington, DC

Abstract: BackgroundThe COVID-19 pandemic has had far-reaching effects on healthcare systems and society with resultant impact on trauma systems worldwide. This study evaluates the impact the pandemic has had in the Washington, DC Metropolitan Region as compared with similar months in 2019.DesignA retrospective multicenter study of all adult trauma centers in the Washington, DC region was conducted using trauma registry data between January 1, 2019 and May 31, 2020. March 1, 2020 through May 31, 2020 was defined as COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 15 publications
11
42
0
Order By: Relevance
“…This was consistent with previously reported patterns of trauma during the COVID-19 pandemic suggest decreased total trauma volume with statistically significant decreases in blunt injury and concomitant marginal increases in penetrating trauma during the COVID-19 pandemic. [15] , [16] , [17] , [18] , [19] , [20] Results from the present study refine and elaborate upon described changes in patterns of trauma during the pandemic by showing region specific responses in trauma patterns to implemented SAHOs.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This was consistent with previously reported patterns of trauma during the COVID-19 pandemic suggest decreased total trauma volume with statistically significant decreases in blunt injury and concomitant marginal increases in penetrating trauma during the COVID-19 pandemic. [15] , [16] , [17] , [18] , [19] , [20] Results from the present study refine and elaborate upon described changes in patterns of trauma during the pandemic by showing region specific responses in trauma patterns to implemented SAHOs.…”
Section: Discussionsupporting
confidence: 77%
“…Many single institution or single-region investigations completed by the academic trauma community reported a significant decrease in total trauma volume with a minor yet important shift towards higher proportions of penetrating injuries during the first part of the COVID-19 pandemic. [15] , [16] , [17] , [18] , [19] , [20] …”
Section: Introductionmentioning
confidence: 99%
“…The total number was increased in 2020 compared to 2019 but did not demonstrate statistical significance. This trend has been demonstrated by studies conducted in Washington DC, Philadelphia, and London with similar results [30][31][32]. Future pandemics may lead to similar trends.…”
Section: Discussionsupporting
confidence: 78%
“…Chodos et al reported that penetrating trauma increased significantly during COVID-19, and other mechanisms, including falls and motor vehicle accidents, showed no change during COVID-19 in Washington DC. [ 7 ] Sephton et al reported that all the injury patterns were reduced, except for pushbike-related accidents. [ 8 ] Maletizke et al also reported that the proportion of household injuries, bicycle accidents, and domestic violence increased during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%